Are protected areas conserving primate habitat in Indonesia? - Gaveau, D.L.A.; Wich, S.A.; Marshall, A.J. (Oxford University Press, 2016)
Most governments, international institutions, and conservation bodies consider that establishing protected areas represents the best strategy for reducing tropical deforestation and conserving the intrinsic biodiversity of tropical forests. This chapter considers to what extent this is true for the conservation of arboreal primates’ favoured habitats, that is natural old-growth forests, using Indonesia as a case study. The major threats to Indonesian terrestrial protected areas are reviewed and the challenges that must be overcome if these threats are to be effectively countered are described; it is proposed to combine protected areas with natural forest timber concessions to sustain larger forest landscapes than would be possible via protected areas alone.